Clinical characteristics and prevalence of vitamin D insufficiency in children less than two years of age - Ji Hyun Yoon; Cheong Soo Park; Ji Young Seo; Yun Sun Choi; Young Min Ahn (Korean Journal of Pediatrics, 2011)
PurposeTo evaluate the clinical characteristics of vitamin D deficiency and its association with iron deficiency anemia (IDA).MethodsA total of 171 children aged less than two years underwent 25-hydroxyvitamin D3 tests between January 2007 and July 2009. The study was classified into two groups: normal and vitamin D insufficiency, by their vitamin 25-hydroxyvitamin D3 levels.ResultsIn total, 120 children were in the normal group (mean age, body weight and heights 12.5±7.0, 9.3±0.9 kg and 76.8±1.1 cm), and 51 children in the vitamin D insufficiency group (9.9±5.4 months, 9.0±0.9 kg and 75.1±0.9 cm). Vitamin D insufficiency was most commonly diagnosed in the spring (44%). The proportion of complete breast-feeding was higher in the insufficiency (92%), and 25.5% of the children in the deficient group also experienced IDA compared that 12% of normal group. Ten children in the insufficiency group experienced bony changes. Six children received calcitriol medication in the normal group, in whom the mean vitamin 25-hydroxyvitamin D3 level increased from 39.6±14.6 ng/mL (pre-medication) to 41.8±17.2 ng/mL (post-medication), and 13 in the insufficiency group, in whom the mean vitamin 25-hydroxyvitamin D3 increased from 20.7±7.0 ng/mL to a mean post-treatment level of 43.7±23.8 ng/mL.ConclusionThis study demonstrated that approximately 30% of children aged ≤2 years experienced vitamin D insufficiency associated with subclinical rickets. Many children also experienced concurrent IDA. Guidelines for vitamin D supplement in such children must therefore be established.